Effects of frequency and voltage on the output of CMOS-MEMS device - Basuwaqi, A.M. (IEEE Computer Society, 2018)
This research work focuses on performance analysis of a Complementary Metal Oxide Semiconductor-Microelectromechanical System (CMOS-MEMS) device which has been designed and fabricated for humidity sensing purpose. The sensor was designed following the standard 0.35 Î¼m CMOS technology. The device is working using electrothermal principle. Alternative current is supplied to its embedded heater which results in moving the thin film. The sensing principle is based on the change in amplitude of the device due to adsorption or absorption of humidity on the active material layer of titanium dioxide (TiO2) nanoparticles deposited on the moving plate, which results in changing the mass of the device. Although the sensor showed a response to the increase and decrease of humidity, its output signal was nonlinear. To investigate the factors that lead to nonlinear output, the sensor has to be investigated before it is deposited to determine the base output of the sensor. In this paper, the device was tested at low frequency range of 1 Hz to 5 Hz, and the applied voltage was in range of 1 Vrms to 4 Vrms. Wheatstone quarter and half bridge configurations were used to carry out the experimental process. It is observed that the best linear output of the device was achieved at 3 Vrms and 3.5 Vrms. Furthermore, the linearity has improved using Wheatstone half bridge configuration by 6.6 and 11.14 at 3 Vrms and at 3.5 Vrms, respectively. Â© 2017 IEEE.